Utilization of Phytase to Overcome Phytic Acid in Broiler Diet - hidayat, cecep (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Phytic acid has been considered as an antinutrient in broiler diet due to its strong chelator of divalent minerals. Phytic acid has ability for binding positively charged proteins, amino acids, and/or multivalent cations or minerals. The resulting complexes are insoluble, difficult to be hydrolyzed during digestion in poultry, and thus, nutritionally less available for absorption. The reduction of phytate activity can be carried out by phytase supplementation. The application of phytase with respect to animal feed supplement is reviewed in this paper. Application of phytase in broiler diet may liberate cations and other nutrients bound by phytate-P complexes resulting in improved production parameters in broilers. This is because phytase supplement increased nutrient (protein, minerals, amino acid, energy, and carbohydrate) digestibilities and availabilities. Overall, phytase could increase nutrient utilization in broiler, hence, increase the economic efficiency of broiler production and reduce the phosphor pollution to the environment. Â  Â  Â